Lower risk of pelvic metalware infection with operative repair of concurrent bladder rupture. Issue 6 (9th November 2017) - Yao, Henry H.‐I.; Esser, Max; Grummet, Jeremy; Atkins, Chris; Royce, Peter; Hanegbi, Uri
Abstract : Background: Patients with traumatic bladder rupture frequently have associated pelvic fracture. With increasing numbers of pelvic fractures fixed internally, there are concerns that conservative management of bladder rupture may increase the risk of pelvic metalware infection. This study aims to determine if operative repair of bladder rupture in comparison to conservative management with catheter drainage alone is associated with a lower rate of infection of internal fixation device for concurrent pelvic fracture. Methods: This is a retrospective cohort study of level IV evidence. From July 2001 through June 2013, 45 multi‐trauma patients at a level 1 trauma centre were identified to have sustained bladder rupture with concurrent pelvic fracture requiring internal fixation. Clinicopathological data were extracted from the TraumaNET database, medical records and health‐coding database. Patients were stratified into two retrospective cohorts, management with surgical repair and management with catheter drainage alone. Fischer's exact test was used to determine whether the rate of pelvic metalware infection was different in the two cohorts. Results: Of the 45 patients, 13 had intraperitoneal bladder rupture, 28 had extraperitoneal bladder rupture and four had combined intra‐extraperitoneal bladder rupture. The median age for this cohort was 31. Bladder rupture was surgically repaired in 36 patients and managed conservatively with catheter drainage in nine patients. The rate of pelvic internal fixation device infection was lower in patients managed with surgical repair compared with conservative management (5.6% versus 33.3%, P = 0.047). Conclusion: Operative repair of bladder rupture is associated with a lower rate of pelvic orthopaedic hardware infection in the presence of concurrent pelvic fracture requiring internal fixation.